Transformational Leadership, Work Motivation, and Their Influence on Employee Performance: Evidence from the Office of Supervision and Customs Services Type Madya Pabean a Pasuruan - Febrianto, Dhimas Bagus Wahyu; Sundjoto, Sundjoto; Rahayu, Sri; Fitrianty, Rifda (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This paper investigates the influence of Transformational Leadership and Work Motivation on Employee Performance at KPPBC TMP A Pasuruan. Employing a quantitative methodology, the study utilizes structured questionnaires based on a Likert scale, and is designed as explanatory research to analyze the causal effects of leadership style and employee motivation on performance outcomes. A randomly selected sample of 43 employees participated in the survey, and the collected data were analyzed using multiple linear regression techniques. The findings reveal that both transformational leadership and work motivation have significant individual positive effects on employee performance. Moreover, when examined together, these two factors explain a substantial portion of the variability in performance outcomes. This underscores the critical role of leaders who not only provide vision, direction, and support but also foster a motivating work environment that encourages commitment, engagement, and productivity. The results align with theoretical frameworks on leadership and motivation and contribute to the literature by reinforcing how these factors operate within public sector organizations. The study offers practical value for administrators and policymakers, suggesting that cultivating transformational leadership behaviors and strengthening motivational strategies can improve employee output, efficiency, and service quality. By doing so, public institutions like customs offices can enhance organizational performance and better fulfill their service mandates. The research also provides empirical evidence that can guide future academic studies and management practices in similar institutional contexts.